Boosting Teacher Performance Through Competence, Allowance, And Training: The Role of Motivation at H. Moenadi Vocational School - Puspitasari, Wendy; Raharjo, Tri Joko; Utomo, Cahyo Budi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Teacher performance reflects their work, encompassing their knowledge, skills, values, and attitudes in fulfilling their duties and responsibilities. This performance is evident in their appearance, actions, and achievements. This study investigates the impact of teacher competence, professional allowances, and skills training on teacher performance, with work motivation as an intervening variable. The research employs a quantitative methodology. The study's subjects comprised all 57 teachers at H. Moenadi Ungaran State Vocational High School, utilizing a saturated sampling method due to the small population size. Data was collected using a questionnaire that had undergone validity and reliability testing. The findings indicate that teacher competence, professional allowances, and skills training collectively influence teacher performance through work motivation as an intervening variable.